Functional role of the C‐terminal tail of the archaeal ribosomal stalk in recruitment of two elongation factors to the sarcin/ricin loop of 23S rRNA. (2nd June 2015) - Imai, Hirotatsu; Miyoshi, Tomohiro; Murakami, Ryo; Ito, Kosuke; Ishino, Yoshizumi; Uchiumi, Toshio
<x xml:space="preserve">Abstract</x> Two types of elongation factors alternate in their binding to the factor‐binding center of the ribosome. The multi‐copy ribosomal protein family, termed the stalk, contributes actively to the factor recruitment. Our results suggest a crucial role for the interactions between the stalk C‐terminal tail and elongation factors in their recruitment to the SRL of 23S rRNA within the ribosome.